1982
DOI: 10.1159/000225677
|View full text |Cite
|
Sign up to set email alerts
|

CFU-s and CFU-c Proliferation after Treatment of Normal Bone Marrow Cells with Ehrlich Ascitic Fluid

Abstract: The possible role of some soluble factor produced by tumor cells or by tumor-host interaction on homeostatic mechanism of normal bone marrow was investigated. Our data show that the in vitro pre treatment of normal bone marrow cells with Ehrlich acellular ascitic fluid (EAF) produces a severe reduction of the number of colonies either in CFU-s (colony-forming unit-spleen assay for pluripotent stem cell compartment) or in CFU-c (colony-forming unit-culture test for granulocytic committed compartment). The diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Influence of tumour growth on the immune system and on the hematopoietic activity has been suggested by several authors (Pessina et al, 1982b;Staszewski, 1997). Evaluation of integrity of hematopoiesis in the bone marrow is important to understand how a compound alters blood cell production and how these changes collectively affect the immune status of the host.…”
Section: Discussionmentioning
confidence: 95%
“…Influence of tumour growth on the immune system and on the hematopoietic activity has been suggested by several authors (Pessina et al, 1982b;Staszewski, 1997). Evaluation of integrity of hematopoiesis in the bone marrow is important to understand how a compound alters blood cell production and how these changes collectively affect the immune status of the host.…”
Section: Discussionmentioning
confidence: 95%
“…What is perhaps of interest is the experimental evidence that the Ehrlich ascites tumor produces an immunosuppressive effect by depletion of macrophage functions, as a mechanism of evasion of the tumor from the host defenses (14,15,(27)(28)(29)(30)(31)(32). Additionally, studies from our laboratory (33,34) and others (14,15,28,(35)(36)(37)(38) have shown the ability of the Ehrlich ascites tumor to affect the receptor system of granulocyte-macrophage progenitor cells and a number of the functional capabilities of macrophages. Fecchio et al (15) have shown that the Ehrlich ascites tumor induces a poor inflammatory response, since…”
Section: Introductionmentioning
confidence: 96%
“…The empirical ethnopharmacological use of E. tirucalli L. as an antitumoral agent in association with the conflicting in vitro data found in the literature regarding its biological properties led us to investigate the myeloprotective properties of E. tirucalli L. on the Ehrlich ascites tumour (EAT) model. This tumour model induces profound alterations in the bone marrow compartment, as expressed by a decline in the number of progenitor cells, particularly of the macrophage and granulocyte lineage, with the presence of extramedullar hematopoiesis [9,10]. It is generally accepted that the decrease in bone marrow progenitor cells is associated to a massive migration out of the marrow, via the blood, leading to an accumulation in the spleen.…”
Section: Introductionmentioning
confidence: 99%